Freelance Platform Sebagai Pengelolah Tuan Tanah: Struktur Tekno-Feodalisme dalam Ekonomi Platform Ilustrator - Akhyani, Faizal (Universitas Muhammadiyah Sorong, 2025)
On platforms such as Fiverr and Upwork, the relationship between workers, clients, and companies is organized into a new structure that resembles feudalism: the platform acts as a digital landlord extracting rent from every interaction, while the algorithm replaces the overseer in regulating the rhythm of production. Through a phenomenological ethnographic approach to illustrators in Indonesia, work experiences are recorded as a constant negotiation between freedom and control. Ratings, reviews, and response speed become indicators that determine visibility while simultaneously shaping the workers’ emotional consciousness. Anxiety, communication strategies, and self-management emerge as responses to the algorithmic power that continuously monitors them. The flexibility often promised by the platform transforms into a new disciplinary mechanism that subdues creativity under the logic of data. Within this digital space, immaterial labor intertwines with techno-feudal power, where creativity, emotion, and lived experience are ensnared within a rent structure no longer grounded in land, but in networks and algorithms.